The Role of Islamic Economics and Finance in Activating Sustainable Development - Hayder Ali Kadhim Al Fatlawi; Wasan Khifah Abdulridha ALsaedi; Saim Kayadibi (Zien Journals, 2022)
Novelty: Because of the sabotage that afflicted nature, such as air pollution, depletion of natural resources, the problem of carbon, and others, the ideas of the green economy and the ideas of sustainable development, which develop human well-being and preserve the right of future generations to natural resources, have emerged.
Keywords: Islamic Economics; sustainable development; Islamic Finance; Endowment